2016
DOI: 10.1002/cpe.3855
|View full text |Cite
|
Sign up to set email alerts
|

Forensic data acquisition from cloud‐of‐things devices: windows Smartphones as a case study

Abstract: The continued amalgamation of cloud technologies into all aspects of our daily lives and the technologies we use (i.e. cloud-of-things) creates business opportunities, security and privacy risks, and investigative challenges (in the event of a cybersecurity incident). This study examines the extent to which data acquisition from Windows phone, a common cloud-of-thing device, is supported by three popular mobile forensics tools. The effect of device settings modification (i.e. enabling screen lock and device re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 21 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…A successful attack on the IoT infrastructure can have crippling effects. For example, compromise of IoT services in smart cities could easily lead to a major chaos or even life threatening situations (see [58], [59], [60]). In this paper, a model with two-layer dimension reduction and classification was proposed.…”
Section: B Real-world Applicationsmentioning
confidence: 99%
“…A successful attack on the IoT infrastructure can have crippling effects. For example, compromise of IoT services in smart cities could easily lead to a major chaos or even life threatening situations (see [58], [59], [60]). In this paper, a model with two-layer dimension reduction and classification was proposed.…”
Section: B Real-world Applicationsmentioning
confidence: 99%
“…As a result, the researchers have determined that the power status of the mobile devices matter because a data alteration issue may occur if the device power state was not correctly handled at the beginning of the acquisition process. The result also revealed that support for Windows Phone devices by the tested mobile forensic tools was still limited [39].…”
Section: Evidence Collection and Acquisitionmentioning
confidence: 78%
“…This final phase relates to the preparation and presentation of the information resulting from the analysis phase. As observed by Cahyani et al [68], [69], [70], it is important for forensics examiners to articulate and explain complex and technical forensic terminologies to the judiciary and juries in order for them to understand "how these crimes were committed, what digital evidence is and where it may exist, and how the process of digital evidence collection was undertaken by the forensic investigators" [71].…”
Section: Methodsmentioning
confidence: 99%